2013
DOI: 10.3109/10641963.2013.776572
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non-dipper and Dipper Blood Pressure Patterns on Aortic Elasticity in Patients with Metabolic Syndrome

Abstract: The purpose of this study was to evaluate the effect of blood pressure (BP) rhythm on aortic functions in patients with metabolic syndrome. Seventy patients with newly diagnosed hypertension who fulfilled the metabolic syndrome criteria according to the Third Report of the National Cholesterol Education Program Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (NCEP/ATP-III) were evaluated with 24-hour BP holter monitoring. According to BP rhythm, 35 patients with dipper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous research has shown that 24-h ambulatory blood pressure monitoring (ABPM) is a better predictor of subsequent complications than spot measurements of blood pressure [5,6]. More recent study has shown that metabolic syndrome has a deleterious effect on aortic function [7]. Further, the effect of non-dipping BP on aortic root diameter in patients with metabolic syndrome has yet to be sufficiently investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Previous research has shown that 24-h ambulatory blood pressure monitoring (ABPM) is a better predictor of subsequent complications than spot measurements of blood pressure [5,6]. More recent study has shown that metabolic syndrome has a deleterious effect on aortic function [7]. Further, the effect of non-dipping BP on aortic root diameter in patients with metabolic syndrome has yet to be sufficiently investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Kim et al [36] reported that endothelial progenitor cells, which play a key role in endothelial homeostasis and vascular repair, are less prevalent in the circulation of nondipper than dipper HT patients. In addition, aortic stiffness, which increases with atherosclerosis and endothelial dysfunction [37], has been shown to be increased in non-dipper HT patients compared with dipper HT patients [38,39]. Considering that NGAL, which is regarded as a plasma marker of neutrophil activation, increases in endothelial dysfunction and contributes to the development of atherosclerosis [13,40], the high serum NGAL concentrations found in non-dipper HT patients might be due to endothelial dysfunction, which is more prevalent in non-dipper HT patients.…”
Section: Discussionmentioning
confidence: 99%